KUALITAS UMBI BEBERAPA KLON KENTANG (Solanum tuberosum L.) DATARAN MEDIUM UNTUK KERIPIK - Ali Asgar (BERITA BIOLOGI, 2013)
Quality testing of several potato clones (Solanum tuberosum L.) planted at mid level area for potato chips. Objective of the research is to test the quality of clones/cultivars resulted from selection. Quality test of 8 selective clones was conducted from November 2010 to February 2011 in post-harvest laboratory of Research Institute for Vegetables Lembang. Research was arranged in randomized complete block design with 4 replications. Treatments consisted of 1) klon 395195.7, 2) klon 397073.7, 3) Granola (control), 4) Merbabu-17(control), 5) 394614.117, 6) CIP 3970.77.16, 7) CIP 391846.5, and 8) CIP 394613.32. The result of research showed that differences in potato clones (as raw material) have different characteristic on specific gravity, dry matter, reducing sugar content, moisture content, starch content. There were also differences in oil content, color, flavor, crispyness and appearance of chips produced. The best clones for potato chips were Merbabu-17 (specific gravity 1.08 g/ml, dry matter 11.18%, reduction sugar 0.60%, moisture content 88.82%, starch content 4.52% and fat content of chips 38.66%), and CIP394613.32 (specific gravity 0.99, dry ingredient 12.17%, reduced sugar 0.09%, moisture content 87.83%, starch content 3.50%, fat content of chips 28.25%), and Granola (specific gravity 1.02, dry matter 17.70%, reduction sugar 0.12%, moisture content 82.30%, starch content 6.67%, fat content of chips 38.21%).